A relação entre desenvolvimento cognitivo e estimulação precoce em alunos da 4. serie do 1. grau - Marmulsztejn, Lucia (1980)
The present study had the main of vergying experimentally the influence of the early stimulation in the cognitive development. The idea of this study arose from the importance that isatributed to the problem of a bitter utilization of the Man in his potencialities for the construction of a better humanity. Such possibility is reflected primarily in the heart of the educational process, particularly, the school. It was based, Theoretically, in Gerome Brumer, having two of his.proposition as its center: any subject can be taught afficiently, in an honest way, to any development stage; he main purpose of education is to reach immaturity, leading man to be more productive, more adjusted in his culture, developing his potencialities or going beyond them to create more. Looking for a better fundamentation, the author based herself in Theoretical and experimental studies of Piaget, Montessori, Okon, Poppovic, Oslon, Austin & Postlethwaite and others besides some research done by brasilian authors or institution. The study was addressed, specifically to 4th grade students, to measure pedagogical competence and to know some data referent to initial scholorization. The results obtaines confirmes the fundamental hypotesis: 'the earlier a chilot is stimulated, the bigger be her later pedagogical competence, what is thought to be due to the aceleration of her cognitive development. Otherwise, due to the delimitation created and to its suffered limitations, the author suggests the realization of ulterior researches about the same topic, so that could be proposed, based on a more consistent experimental data and of greater extent a psychopedagogical use adapted to the social and technological reality of our Time.